2010
DOI: 10.1371/journal.pone.0010717
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for SARS Transmission from Patients Requiring Intubation: A Multicentre Investigation in Toronto, Canada

Abstract: BackgroundIn the 2003 Toronto SARS outbreak, SARS-CoV was transmitted in hospitals despite adherence to infection control procedures. Considerable controversy resulted regarding which procedures and behaviours were associated with the greatest risk of SARS-CoV transmission.MethodsA retrospective cohort study was conducted to identify risk factors for transmission of SARS-CoV during intubation from laboratory confirmed SARS patients to HCWs involved in their care. All SARS patients requiring intubation during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
308
2
20

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(344 citation statements)
references
References 28 publications
7
308
2
20
Order By: Relevance
“…1 Specific medical procedures that aerosolize respiratory secretions were associated with outbreaks among health care workers, including resuscitation, positive airway pressure ventilation, and endotracheal intubation. [36][37][38][39][40][41] These medical procedures also require workers to be in proximity to patients, so it is not possible to retrospectively attribute exposures to specific routes of transmission. No experimental studies in humans have demonstrated transmission of SARS by aerosol or any other route.…”
Section: Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%
“…1 Specific medical procedures that aerosolize respiratory secretions were associated with outbreaks among health care workers, including resuscitation, positive airway pressure ventilation, and endotracheal intubation. [36][37][38][39][40][41] These medical procedures also require workers to be in proximity to patients, so it is not possible to retrospectively attribute exposures to specific routes of transmission. No experimental studies in humans have demonstrated transmission of SARS by aerosol or any other route.…”
Section: Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%
“…CDC guidelines recommend ocular protection in conjunction with respiratory protection during laboratory or occupational exposure to respiratory viruses (6), but these recommendations are not stringently observed, and numerous cases of ocular complications have been reported for individuals wearing respiratory protection in the absence of eye protection (1,7,8). Despite this, the relative risk of acquiring a respiratory infection via ocular exposure has not been examined.…”
mentioning
confidence: 99%
“…No other procedures emerged with such a clear association. There were 2 studies reported for non-invasive ventilation which demonstrated a pooled OR of 3.1, but they were low quality studies in which the association in one was not statistically significant [20] and the other was also not significant after multivariate analysis [21]. On the basis of the review, the WHO has made a strong recommendation in the recently revised ARI guideline that identifies intubation for special attention as a procedure associated with risk of transmission of respiratory viruses [8] (see recommendations 6 and 7 in Table 2).…”
Section: Aerosol Generating Proceduresmentioning
confidence: 99%